The new plantation : Black athletes, college sports, and predominantly White NCAA institutions - Hawkins, Billy Joe. (New York : Palgrave Macmillan, 2010)
The New Plantation examines the controversial relationship between predominantly White NCAA Division I Institutions (PWI's) and black athletes, utilizing an internal colonial model. It provides a much-needed in-depth analysis to fully comprehend the magnitude of the forces at work that impact black athletes' experiences at PWI's.
Brief historical overview and the experience of Black athletes and students at predominantly White institutions : a mind is a terrible thing to waste -- The new plantation model : a conceptual framework for diagnosing the experiences of Black athletes at predominantly White NCAA division I institutions -- Intellectually inferior and physically superior : racist ideologies and the Black athlete -- Operating in the "black" financially : on the back of the Black athletic body -- The Black athlete's racialized experiences and the predominantly White intercollegiate institution -- The sociocultural environment of predominantly White NCAA institutions : the Black athlete as oscillating migrant laborers -- Politics and the Black athletic experience -- Friday night lights : a dream deferred or delusions of grandeur -- Athletic reform and decolonization.
Includes bibliographical references and index.
Keywords: National Collegiate Athletic Association; African American athletes -- Social conditions; African American college students -- Social conditions; College sports -- United States; Racism in sports -- United States; Racism in education -- United States; United States -- Race relations